Interaction of West-Nile virus capsid protein with lipid systems - Martins, Ana de Souto (2016)
West-Nile Virus (WNV) infection occurs through the bite of Culexspp. mosquitoes and constitutes a serious public health threat. Despite the global spread and disease severity, there is no specific and effective treatment for WNV infection, in part due to a poor understanding of the virus life cycle. A key viral life cycle step is viral assembly and encapsidation, mediated by the capsid (C) protein interaction with RNA and host lipid structures. WNVC interactionswith intracellular lipid droplets (LDs) and with very low-density lipoproteins (VLDL), crucial step for successful viral replication in related members of the Flaviviridaefamily, were studied via biophysical approaches. Zeta potential measurements showed that WNVC interaction with LDs requires K+and LDs surface proteins. WNVC interaction with lipoproteins measured via dynamic light scattering(DLS), showed that WNVC binds to VLDL but not tolow-density lipoproteins(LDL), in a potassium dependent manner. It was clear that in the presence of WNV C there is an increase of the VLDL hydrodynamic radius that correlates very well with WNV C estimated dimension. The WNVC (un)binding forcesupon interaction with LDs and VLDL werequantitatively determined by atomic force microscopy(AFM)-based force spectroscopy. WNV C specifically binds to LDs and VLDL, in a potassium-dependent manner,but not to LDL.DLS was also performed todetermine pep14-23 (an inhibitor of dengue virus–DENV –Cproteininteraction with LDs and VLDL) effect on WNVC-VLDLbinding. Data obtained indicate that pep14-23 may also be a potential inhibitor for WNVC key interactions.The results obtained in this study are in agreement with thepreviouslyobserved forDENV, showing that WNV C and DENV C proteins interact in a similar manner with LDs and VLDL, and suggesting pep14-23 asa potential inhibitor of FlavivirusC proteinsbinding tohost lipid systems.